THE IDEAS OF INTERNATIONAL SOLIDARITY IN THE EASTERN CYCLE OF POEMS "TWO STREAMS" AND THE STORIES OF "SIX COLUMNS" BY N.S.TIKHONOV - Kazimov, Kamran (Gênero & Direito, 2020)
The article discusses the series of poems "Two streams" by a prominent figure of XX century russian poetry N.S.Tikhonov. The ideas of international solidarity, reflected by the poet in these poems are investigated. The poem titled "The Night of Eternity", which was included in the book titled "Braga" (1922) by N.Tikhonov, was the first proof of the strengthening of friendship between the Arab and Soviet nations.The cunning and observing craftsman clearly reveals what he saw in his new stories in Beirut and in Damascus. He listened to midnight friendly conversations and public literary sessions. "The six columns" is a book of stories and narratives by N.Tikhonov. These works are based on the impression that a distinguished writer gained during his journeys to the Middle East and Southeast Asia. Between 1949 and 1962, the peoples of these countries broke the colonial chain and embarked on an independent path of development.